2017
DOI: 10.1007/s40653-017-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Legacies of Childhood Victimization: Indirect Effects on Adult Mental Health Through Re-Victimization

Abstract: The objective of the current study was to evaluate the direct and indirect effects of childhood victimization on adult mental health, focusing on adult re-victimization as a mediator. Participants (n = 279) were recruited via Amazon Mechanical Turk reported on childhood victimization, adulthood victimization, and current mental health. Sixty percent of the sample reported at least one incident of re-victimization in adulthood. Three regressions were conducted in SPSS using the PROCESS macro for mediation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Characteristics of victimization and revictimization in our study were also strikingly similar to another study that used the JVQ with mostly White, female adults (ages 19–62 years), which reported the exact same order for most common subtypes of childhood victimization experiences and a 59.5% rate of revictimization in adulthood (Scrafford et al, 2018). Of note, we did not control for participant gender as this was not related to the dependent variable, number of adulthood victimization experiences.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Characteristics of victimization and revictimization in our study were also strikingly similar to another study that used the JVQ with mostly White, female adults (ages 19–62 years), which reported the exact same order for most common subtypes of childhood victimization experiences and a 59.5% rate of revictimization in adulthood (Scrafford et al, 2018). Of note, we did not control for participant gender as this was not related to the dependent variable, number of adulthood victimization experiences.…”
Section: Discussionsupporting
confidence: 85%
“…It is notable that our findings replicated that of this study by Finkelhor and colleagues when we used a modified version of the JVQ and five different measures of adulthood victimization. These findings suggest that future revictimization research should continue to examine various victimization types, as limiting examination of revictimization to one type is likely to underestimate the full burden of broader victimization that these individuals experience (Hamby et al, 2017; Scrafford et al, 2018; Turner et al, 2010). Furthermore, future research should examine relationships between distinct types of victimization to further understand which types may pose the greatest risk for others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated annual cost of childhood fatal and nonfatal maltreatment in the USA in 2015 was 2.0 USD trillion, and this does not include the quality of life costs in pain and suffering experienced by maltreated children before they reach adulthood (Peterson, Florence, & Klevens, 2018). With the high risk of adult re-victimization experienced by children who are victimized and have mental health problems (Lee, 2015;Papalia et al, 2017;Ports, Ford, & Merrick, 2015;Scrafford, Grein, & Miller-Graff, 2018), the lifetime economic burden may be severe: the estimated annual cost of rape in the USA in 2014 was 3.1 USD trillion (Peterson, DeGue, Florence, & Lokey, 2017) and the cost of intimate partner violence in 2015 was 3.6 USD trillion , 50-60% of which was due to medical costs.…”
mentioning
confidence: 99%